Functional connectivity patterns of the Giant Toad Rhinella horribilis in anthropogenically modified landscapes - Gerardo J. Soria-Ortiz; Leticia M. Ochoa-Ochoa; Juan P. Jaramillo-Correa; Íñigo Martínez-Solano; Ella Vázquez-Domínguez (PLoS ONE, 2025)
Anthropized environments often fragment native habitats and alter the movement of individuals across the modified landscape mosaic, which is significantly challenging for wild species. Deciphering the environmental factors associated with population genetic patterns in modified habitats is essential to understand functional connectivity and for the conservation of wild populations inhabiting increasingly modified habitats. We used ddRAD-seq genomic data to study the genetic diversity, genetic structure and functional connectivity of the Giant Toad, Rhinella horribilis populations across two landscapes with distinct levels of habitat modification. We also applied a landscape genetics approach to identify landscape variables (climatic, vegetation, water bodies, land use) associated with the toad’s functional connectivity in both landscapes. Structure analysis between the two landscapes show that they are genetically differentiated given their distinct degree of habitat modification. Within landscapes, our results identified lower genetic diversity, higher genetic structure and lower functional connectivity among R. horribilis populations in the landscape with higher habitat modification. Results also demonstrate that structure and functional connectivity are significantly influenced by barriers like rivers and roads. Furthermore, water bodies availability was the most important landscape feature for R. horribilis connectivity, whereas vegetation cover, solar radiation and relative humidity also played a significant role. Our study illustrates how landscape features in modified habitats can differently determine genetic diversity and functional connectivity patterns, and highlights the importance of working with often-disregarded common species like the Giant Toad. Prioritizing the management of water bodies in our study sites and elsewhere would be essential to sustain amphibian population dynamics, enhancing individual movement and genetic exchange.